Workshop Storytelling Saintifik Berbasis Cerita Rakyat Nusantara untuk Meningkatkan Kompetensi Pedagogis Guru dan Literasi Sains Siswa di Sekolah Indonesia Jeddah - Lintang Kironoratri; Fina Fakhriyah; Siti Masfuah; Much. Arsyad Fardani; Wawan Shokib Rondli (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance teachers' pedagogical capacity through a Scientific Storytelling Workshop and to develop a Scientific Storytelling Teaching Module as a contextual instructional resource based on Indonesian folktales. The program involved five teachers and 30 students from the Indonesian School of Jeddah through a series of activities, including needs assessment, module development, workshop implementation, classroom application, and monitoring and evaluation. Program evaluation was conducted using qualitative analysis based on classroom observations and collaborative reflection with teachers to assess program implementation and module acceptability. The results showed that the workshop was implemented as planned, teachers were able to apply the module in science instruction, and a Scientific Storytelling Teaching Module was successfully developed. The module includes storytelling guidelines, inquiry-based questions, simple science experiments, student worksheets, and cultural reflection activities. Overall, the program supported more contextual science learning while promoting the integration of science literacy and cultural literacy within the school environment.